Criminology characteristics and prevention of juvenile crime - Rohatynska, Nina; Voitiuk, Nadiia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
The article analyzes the criminological characteristics of minors, features of juvenile crime prevention in Ukraine. The current trends in juvenile delinquency in Ukraine are determined. Attention is focused on the features that determine the specifics of crimes committed by minors. At the same time, the study of this topic is also due to the fact that in recent years the number of crimes committed by minors is gradually increasing, and the actions of young offenders are marked by growing cruelty and cynicism. The psychological features and social factors of such crime have been clarified.Juvenile delinquency is one of the most urgent problems, since this category of persons belongs to the most criminally vulnerable social groups, and also acts as one of the most significant indicators of the criminogenic situation in the country. The domestic legal theory needs a thorough study of the problems of juvenile delinquency, which in the future will ensure the effective socio-economic development of our state.Juvenile delinquency is an important and topical topic for many countries of the world, including Ukraine. And all because young people are the future of the state, who will later change and improve social life, as well as build Ukraine. But the problems associated with the insufficient mechanism of crime prevention are quite serious and complex, and such that they require an immediate solution.In Ukraine, in particular, there are many problems related to the prevention of juvenile delinquency, namely: insufficient implementation of preventive measures at various levels, starting from the development of special legal norms and ending with individual work with adolescents who need attention.This article will consider the most pressing problems related to juvenile delinquency in Ukraine, as well as methods of its prevention. The reasons and conditions that encourage minors to commit illegal acts will also be analyzed, the need to take comprehensive measures to combat juvenile delinquency, using their criminological characteristics, will be emphasized.